COVID-19 in Workplaces: Secondary Transmission. Issue 9 (10th August 2021) - Sarti, Donatella; Campanelli, Tamara; Rondina, Tommaso; Gasperini, Beatrice
Abstract: Objectives: Coronavirus disease (COVID-19) contagion at work is well studied for healthcare workers, however it is not enough assessed in other working settings. Very little is known, indeed, about the risk of COVID-19 transmission through occupational exposure in non-health working places. This study aims to describe a COVID-19 cluster among workers in an office in Italy. Methods: This was a retrospective observational study on a cluster of COVID-19 that occurred from 20 November through 3 December 2020 in a group of six colleagues (A–F) working in the same office full time 5 days a week, 8 h a day. The workers used the following prevention measures: social distancing (desks were >1 m, 1.76–5.01 m range), plexiglas panels, hands disinfection, and use of face mask. However, they did not wear face mask when in static position sitting at their desk and they did not aerate the place frequently. Results: The disease spread from one worker (subject A) to four (80%) of the five colleagues (subjects B–F). Only subject D was negative to COVID-19 on 14 days after last contact with subject A (20 November 2020) as confirmed by nasopharyngeal swab testing. Subject D, in particular, did not contact subject A in the 48 h before symptoms onset. COVID-19 positivity of subject A was promptly communicated to the colleagues, who started self-isolation from their relatives and none of their households were infected. COVID-19 transmission was observed only in households of subject A. Conclusions: The rapid communication of COVID-19 positivity to the colleagues and the prompt isolation of index case's close contacts allowed to eliminate the secondary transmission to their households. The contagion of index case's colleagues occurred from second day before symptoms onset. Distancing of >1 m, use of plexiglass panels, sanitizing hand gel, and inconstant use of face mask may not be enough for infection prevention in closed places with poor ventilation and high occupancy.